The Relationship between Social Attitudes and Student Chemistry Learning Outcomes During the Covid-19 Pandemic - Rofiah, Rofiah; Purwoko, Agus Abhi; Andayani, Yayuk (IJECA (International Journal of Education and Curriculum Application), 2022)
This study aims to describe the relationship between social attitudes and student chemistry learning outcomes during the Covid-19 pandemic. This type of ex-post facto quantitative research involved 203 students of class XII science which was determined by using multistage random sampling technique from a total population of 406 students at Madrasah Aliyah Mataram. Social attitude data were obtained from questionnaires and learning outcomes data were obtained from description questions on the colligative properties of solutions. The results of the descriptive analysis showed that the categories for social attitudes and student chemistry learning outcomes were in the moderate category with a percentage of 68,5% and 66%, respectively. Of the seven element of social attitudes, the highest value is found in the element of tolerance and the lowest value is found in the honest element. The results of the analysis show that social attitudes and student chemistry learning outcomes during the Covid-19 pandemic have a positive and significant relationship although it is very low (rxy = 0,24). Based on these results, it can be concluded that social attitudes can affect student chemistry learning outcomes during the Covid-19 pandemic in class XII IPA at Madrasah Aliyah Mataram, although the effect is relatively low. It is hoped that these findings will be taken into consideration by schools so that they can take appropriate policies so that student learning outcomes are better.